FEATURES OF THE FUNCTIONING MECHANISM OF THE ENTRY SUMMARY DECLARATION IN UKRAINE - KHLIEBNIKOVA, Inna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the issue of the introduction of the institution of the Entry Summary Declaration in Ukraine and reveals the peculiarities of the mechanism of its functioning. It has been established that the implementation of the procedure for the submission of the Entry Summary Declaration by carriers for passage through the customs border of Ukraine corresponds to the understanding of its tasks and place in ensuring the security of international supply chains accepted in European practice, and the provided data format fully meets the requirements of European customs legislation.The structural and logical scheme of the procedure for the passage of cargo through the customs border of Ukraine using the Entry Summary Declaration is characterized. It was concluded that the main difference between the Entry Summary Declaration in relation to other customs declarations is that the information from it is subject to processing through risk analysis for the purpose of protection and security before the goods arrive on the territory of Ukraine, and not for calculating the amount of customs payments. Based on the analysis of domestic legal acts, it was established that the implementation of such a tool in the national customs legislation is aimed at identifying batches of goods with a high degree of risk, automating customs procedures to reduce subjectivity, facilitating the work of customs officials in order to achieve greater predictability and predictability of the system customs risk management.Attention is focused on the gradual implementation by the customs authorities of format-logical control (automated verification) of the correctness of filling in the data of the Entry Summary Declaration. It was found that currently, customs authorities apply a limited number of risk profiles, in particular security risks for non-tariff regulation: goods from the Russian Federation (conducting an inspection); non-tariff methods - drugs, precursors, waste. The need for further research in the direction of the development of tools for the detection of cases of violation of customs legislation and assessment of customs risks under the Entry Summary Declaration by profiling customs risks in the automated system of customs clearance is emphasized.
Keywords: Entry Summary Declaration; customs control; analysis of customs risks; international supply chain security